Erucic Acid: A Possible Therapeutic Agent for Neurodegenerative Diseases - Goyal, Ahsas; Dubey, Nandini; Verma, Aanchal; Agrawal, Anant (Current Molecular Medicine, 2024)
Neurodegenerative disorders are among the most common life-threatening disorders among the elderly worldwide and are marked by neuronal death in the brain and spinal cord. Several studies have demonstrated the beneficial role of dietary fatty acids in different brain disorders. This is due to their neurotrophic, antioxidant, and anti-inflammatory properties. Furthermore, extensive evidence shows that an unbalanced intake of certain dietary fatty acids increases the risk of neuropsychiatric diseases. Several research has been done on erucic acid, an ingestible omega-9 fatty acid that is found in Lorenzo's oil. Erucic acid was previously thought to be a natural toxin because of its negative effects on heart muscle function and hepatic steatosis, but it has been discovered that erucic acid is regularly consumed in Asian countries through the consumption of cruciferous vegetables like mustard and rapeseed oil with no evidence of cardiac harm. Erucic acid can also be transformed into nervonic acid, a crucial element of myelin. Therefore, erucic acid may have remyelinating effects, which may be crucial for treating different demyelinating conditions. Also, erucic acid exerts antioxidant and anti-inflammatory effects, suggesting its possible therapeutic role in different neurodegenerative disorders. Considering the fruitful effects of this compound, this article reviews the probable role of erucic acid as a pharmacological agent for treating and managing different neurodegenerative disorders.
Keywords: omega-9 fatty acid